Tools and Strategies for Malaria Control and Elimination: What Do We Need to Achieve a Grand Convergence in Malaria? - Janet Hemingway; Rima Shretta; Timothy N C Wells; David Bell; Abdoulaye A Djimdé; Nicole Achee; Gao Qi (PLoS Biology, 2016)
Progress made in malaria control during the past decade has prompted increasing global dialogue on malaria elimination and eradication. The product development pipeline for malaria has never been stronger, with promising new tools to detect, treat, and prevent malaria, including innovative diagnostics, medicines, vaccines, vector control products, and improved mechanisms for surveillance and response. There are at least 25 projects in the global malaria vaccine pipeline, as well as 47 medicines and 13 vector control products. In addition, there are several next-generation diagnostic tools and reference methods currently in development, with many expected to be introduced in the next decade. The development and adoption of these tools, bolstered by strategies that ensure rapid uptake in target populations, intensified mechanisms for information management, surveillance, and response, and continued financial and political commitment are all essential to achieving global eradication.